Análise da governança de tecnologia da informação para reduzir problemas de agência: estudo em assimetria da informação - Coser, Tiago (Universidade do Vale do Rio dos Sinos, 2015)
The resulting separation issues of ownership and control of capital is directed in this research to the operational level and considers the foundation asymmetry of information. This study examined how the Information Technology (IT) Governance can help reduce agency problems. The agency relationship was established between directors (principal) and managers (agent) of the Administrative and Commercial areas. It is a descriptive research with a qualitative approach, developed through a unique case study in an industry based in the state of Rio Grande do Sul. The main results indicate that agency problems are not limited to information and hidden actions the researched environment, but also are due to weaknesses in resources and information flows supporting the delegation process and monitoring activities among directors and managers. The main contributions of the IT governance to reduce the agency problem are associated primarily to the alignment between IT and business objectives in the planning, construction, delivery and monitoring of IT services. It seeks to standardize business processes and reduce human dependence on the steps of the same.
Keywords: Governança de tecnologia da informação; Problema de agência; Assimetria da informação; Processos de TI; Information technology governance; Agency problem; Information asymmetry; IT processes; COBIT 5; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis